Lignocellulose based on waste biomass material and preparation method thereof
Through the preparation method of waste biomass materials, the problem of shortage of raw materials in the biomass cellulose industry was solved, and lignocellulose with excellent performance was prepared, which solved the problems of recycling and reuse of waste wood and high cost, and realized the biomass cellulose industry stable supply and economic benefits.
Patent Information
- Application Number
- CN202411666919.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The biomass cellulose industry has affected the development of the industry due to the shortage of cotton cellulose raw materials and its dependence on imported lignocellulose.
Methods for preparing lignocellulose using waste biomass materials, including drying, steaming, alkali reaction, cooking and adding DES eutectic solvents, using metal chloride or metal brominated salt catalysts and polyether water-soluble organics As an additive, the lignocellulose with excellent performance is prepared through bleaching, sand removal and concentration processes.
It effectively alleviates the problem of insufficient raw materials, improves the value of scraps under wood, stabilizes the supply of biomass cellulose products, reduces the dependence on foreign lignocellulose, and has good economic benefits and environmental significance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste biomass resource recycling and utilization, and in particular to a kind of lignocellulose based on waste biomass material and a preparation method thereof. Background Art
[0002] Biomass cellulose products are mostly made from cotton cellulose. With the rapid development of the biomass cellulose chemical industry, the demand for cotton cellulose is increasing. However, cotton cellulose is increasingly in short supply due to the constraints of cotton planting area and growth cycle. The limitation of raw materials has seriously affected the development of the biomass cellulose industry, resulting in an increase in the cost of cotton cellulose used in the biomass cellulose industry, and the production costs of downstream textile companies have also increased accordingly.
[0003] At present, domestic enterprises rely heavily on imported cellulose for the production of biomass cellulose products. Lignocellulose has problems such as high price and low yield, which affects the demand for downstream products. Therefore, the development of biomass cellulose to replace part of cotton cellulose has great economic value and social significance. Summary of the invention
[0004] The object of the present invention is to provide a lignocellulose based on waste biomass materials, which has excellent properties.
[0005] Another object of the present invention is to provide a method for preparing lignocellulose based on waste biomass materials. The method is based on waste wood resources and prepares lignocellulose with excellent performance through processes such as drying, steaming, cooking, bleaching, sand removal, and papermaking. It effectively alleviates the problem of insufficient raw materials for existing biomass cellulose products, and at the same time solves the problem of recycling and reuse of waste wood scraps, and has good economic benefits.
[0006] The present invention solves the technical problem by adopting the following technical solutions.
[0007] The present invention provides a method for preparing lignocellulose based on waste biomass materials, comprising the following steps: S1. After drying, steaming, alkali solution reaction and cooking of waste wood, a DES low eutectic solvent is added and mixed to obtain primary lignocellulose, wherein a catalyst and a polyether water-soluble organic additive are added during the cooking, and the catalyst is a metal chloride catalyst or a metal bromide catalyst; S2. The primary lignocellulose is bleached, sanded, concentrated and formed into paper, thereby obtaining lignocellulose.
[0008] The present invention provides a lignocellulose based on waste biomass materials, which is prepared according to the above preparation method.
[0009] The beneficial effects of the lignocellulose based on waste biomass materials and the preparation method thereof according to the embodiments of the present invention are: 1. The present invention firstly uses steam to pretreat the waste wood, which can effectively remove hemicellulose and part of lignin in the raw material, reduce the polypentose content, and thus reduce the amount of alkali solution used. The steaming process will destroy the fiber cell structure, remove the hemicellulose and part of lignin in the intercellular layer and primary cell wall of the fiber cell, so that the alkali solution can more easily penetrate into the cellulose crystallization area during the cooking process, accelerate the delignification reaction, and help improve the cooking effect.
[0010] 2. The present invention adds metal chloride or metal bromide as a catalyst during the cooking process, which can promote the breaking of chemical bonds between glucose molecules in biomass materials and help degrade the macromolecules of wood waste. The addition of polyether water-soluble organic matter as an auxiliary agent is mainly to reduce the interfacial tension of the liquid, which is conducive to the rapid penetration of the reagent into the crystallization area of the wood waste, and facilitates the combination of the added catalyst and the biomass cellulose molecules.
[0011] 3. The present invention makes high-value comprehensive utilization of industrial wood scraps, greatly improves the value of wood, can supply a large amount of materials for downstream enterprises, effectively alleviates the problem of insufficient raw materials for existing biomass cellulose products, ensures that the output of domestic biomass cellulose products is stable and not affected by foreign wood cellulose price fluctuations, and solves the problem of recycling and reuse of waste wood scraps, with good economic benefits. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0013] The following is a detailed description of the lignocellulose based on waste biomass materials and the preparation method thereof according to the embodiments of the present invention.
[0014] The embodiment of the present invention provides a method for preparing lignocellulose based on waste biomass materials, comprising the following steps: S1. After the waste wood is dried, steamed, reacted with alkali solution and boiled, a DES low eutectic solvent is added to mix to obtain primary lignocellulose, wherein a catalyst and a polyether water-soluble organic additive are added during the boiling, and the catalyst is a metal chloride catalyst or a metal bromide catalyst. Specifically, the drying step is: placing the waste wood in a blast drying oven and drying it at 40-60°C, and the moisture content of the dried waste wood is less than 5%.
[0015] The present invention firstly uses steam to pretreat the waste wood to remove sugars in the material. Steaming the waste wood before cooking can effectively remove hemicellulose and part of lignin in the raw material, reduce the content of polypentose, and thus reduce the amount of alkali solution used. The steaming process destroys the fiber cell structure, removes hemicellulose and part of lignin in the intercellular layer and primary cell wall of the fiber cell, so that the alkali solution can more easily penetrate into the cellulose crystallization area during the cooking process, accelerate the delignification reaction, and help improve the cooking effect.
[0016] When the waste wood scraps are boiled, an impregnation aid and a catalyst are added to assist in the preparation of lignocellulose. The present invention selects metal bromide salts or chloride salts as catalysts for preparing lignocellulose, and polyether water-soluble organic matter as an auxiliary agent. Metal bromide salts or chloride salts can promote the chemical bond breakage between glucose molecules in the biomass material during the preparation of lignocellulose, which helps to degrade the macromolecules of wood scraps. Polyether water-soluble organic matter is a non-ionic surfactant, which mainly reduces the interfacial tension of the liquid, facilitates the rapid penetration of the reagent into the crystallization area of the wood scraps, and facilitates the combination of the added catalyst and the biomass cellulose molecules. The present invention first adds an impregnation aid and mixes the wood scraps evenly, and then adds a reaction catalyst so that it can quickly and efficiently enter the interior of the wood scraps, accelerate the oxidation and degradation of wood cellulose, reduce the degree of polymerization of the molecules, and improve the viscosity of lignocellulose.
[0017] Furthermore, in a preferred embodiment of the present invention, the waste wood is selected from one or more of cypress, elm, eucalyptus, and locust wood, and the moisture content of the waste wood after drying is less than 5%, preferably, the moisture content of the waste wood after drying is 0.5-5.0%.
[0018] Furthermore, in a preferred embodiment of the present invention, the steaming step is: putting the dried waste wood into a cooking container, steaming at 160°C to 175°C for 1 to 4 hours, and then discharging the steam in the cooking container. Preferably, the steaming temperature is 160°C to 172°C, and the steaming time is 1 to 2 hours.
[0019] Further, in a preferred embodiment of the present invention, the alkali solution used in the alkali reaction is selected from one of sodium hydroxide solution, potassium hydroxide solution, and calcium hydroxide solution, the concentration of the alkali solution is 30-120 g / L, the alkali solution reaction temperature is 155°C-175°C, and the reaction time is 3-5 hours. Preferably, the alkali solution concentration is 40-120 g / L, the volume ratio of waste wood to alkali solution is 1:2-4; the alkali solution reaction temperature is 158°C-172°C, and the alkali solution reaction time is 3-4.5 hours.
[0020] Further, in a preferred embodiment of the present invention, the polyether water-soluble organic additive is selected from one of polyethylene oxide or polyethylene glycol, the dosage ratio of the polyether water-soluble organic additive to the waste wood is (0.5-10): (1.5-3) mL / kg, the catalyst is selected from one of nickel chloride, cobalt chloride, ferrous chloride, cobalt bromide, and copper bromide, and its addition amount is 0.2-5.0 g / kg, the cooking temperature is 100°C-160°C, and the cooking time is 0.5-1 h. Preferably, the polyether water-soluble organic matter is polyethylene glycol, and its degree of polymerization is 7-15; the metal chloride catalyst is cobalt chloride, and its dosage is 0.2-2.0 g / kg. More preferably, the material purity of polyethylene glycol is 90.0wt%-99.9wt%. More preferably, the material purity of polyethylene glycol is 92.0wt%.
[0021] Further, in a preferred embodiment of the present invention, the DES low eutectic solvent includes an HBA component and an HBD component, the HBA component is CoCL2, NaCL or ChCL, the HBD component is an acidic substance, the mass ratio of the HBA component to the HBD component is 1:1~2, the mixing temperature is 50~80°C, and the mixing time is 20~45 min. The mass ratio of the DES low eutectic solvent and the waste wood is 1~3:1. Preferably, the HBA component is CoCL2, the HBD component is citric acid, HBA:HBD=1:2; the mixing temperature is 60~80°C. The present invention removes the lignin component in the lignocellulose by adding the DES low eutectic solvent during cooking, thereby obtaining primary lignocellulose.
[0022] S2. The primary lignocellulose is bleached, sanded, concentrated and formed into paper, thereby obtaining lignocellulose.
[0023] Further, in a preferred embodiment of the present invention, the bleaching solution used for bleaching includes a bleaching agent and a bleaching aid, the bleaching agent is selected from any one of sodium hypochlorite, hydrogen peroxide, thiourea dioxide, and chlorine dioxide, the bleaching aid is selected from any one of aminosulfonic acid, tetraacetylethylenediamine, and alkyl polyoxyethylene ether, the bleaching temperature is 30°C to 70°C, and the bleaching time is 30 to 60 min. Preferably, the bleaching aid is aminosulfonic acid, and its material purity is 95.0wt% to 99.0wt%. The amount of aminosulfonic acid added as the bleaching aid is 10 to 25 g / kg. More preferably, the amount of aminosulfonic acid added as the bleaching aid is 15 to 20 g / kg. The pulp concentration during bleaching is 3% to 6%.
[0024] When using, first mix the bleaching agent and the bleaching aid to prepare a bleaching solution, and then bleach the cooked cellulose in the bleaching solution. Adding an appropriate amount of aminosulfonic acid during the primary bleaching of cellulose can effectively improve the bleaching effect. Aminosulfonic acid as a bleaching aid can reduce the catalytic effect of metal ions in the bleaching solution, thereby reducing the oxidative degradation of heavy metal ions on cellulose. Aminosulfonic acid will have a fixing effect on the reactive groups of cellulose, prevent the peeling reaction of cellulose molecules, inhibit the degradation of cellulose, thereby increasing the cellulose content and improving the physical strength of cellulose after bleaching.
[0025] Furthermore, in a preferred embodiment of the present invention, the step of sand removal is: controlling the concentration of wood cellulose in the slurry to 0.5% to 2%, the pressure of the sand remover to 0.28 to 0.5 MPa for sand removal, and adding a deashing iron agent after the sand removal, wherein the amount of the deashing iron agent is 0.01% to 0.05% of the mass of the waste wood after drying. Preferably, during the sand removal process, the concentration of wood cellulose is 0.5% to 1.6%, and the pressure of the sand remover is 0.28 to 0.42 MPa.
[0026] Furthermore, in a preferred embodiment of the present invention, the steps of concentrating and forming are as follows: controlling the concentration of the wood cellulose in the concentrator to be 3% to 5%, and using desalted water to form the wood cellulose after concentration, wherein the spraying amount of the desalted water is 25 to 40 m 3 / h. Preferably, the concentration of lignocellulose in the concentrator is controlled to be 3% to 4.5%, and after concentration, lignocellulose is obtained by papermaking in a papermaking machine.
[0027] The present invention prepares lignocellulose based on waste wood resources, which not only avoids the waste of biomass resources, but also can recycle and utilize waste biomass wood resources in a high-value manner, and all indicators of the prepared lignocellulose meet the standards. In actual production, the prepared lignocellulose and cotton cellulose can be used in a certain proportion to produce biomass cellulose products, which has extremely high economic benefits and is suitable for industrial promotion. The present invention provides an innovative method for the further development and utilization of wood waste. According to the advantages of a large output of wood scraps, the demand for lignocellulose by downstream related enterprises can be met, and the purchase cost of plant cellulose by downstream enterprises can be effectively reduced. At the same time, the present invention complies with national policies such as energy conservation and emission reduction, and greatly reduces the amount of forest tree felling.
[0028] The present invention also provides a lignocellulose based on waste biomass materials, which is prepared according to the above-mentioned preparation method. The lignocellulose prepared by the present invention has excellent performance. Among them, the content of lignocellulose is >90.0%, the slurry viscosity (copper ammonia viscosity method) is <25 mPa.s, the reaction performance (viscose filtration method) is <500 s, and the polypentose content is <4.0%, which meets the requirements of using lignocellulose in the biomass chemical industry.
[0029] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0030] Example 1 This embodiment provides a lignocellulose based on waste biomass materials, which is prepared according to the following steps: (1) 1 kg of waste wood was placed in a forced air drying oven and dried at 55°C for later use. Then the dried waste wood was placed in a cooking container and steamed at 170°C for 2 h before the steam in the container was discharged. Then a sodium hydroxide solution with a concentration of 80 g / L was added, the volume of the alkali solution was 4 L, and the temperature was kept at 170°C for 3 h. Then polyethylene glycol and cobalt chloride catalyst were added, wherein the degree of polymerization of polyethylene glycol was 7-15, and the volume / mass ratio of polyether water-soluble organic matter to waste wood raw material was 1.5 mL / kg. The amount of cobalt chloride added was 2.0 g / kg, and the temperature was kept at 160°C for 0.5 h. Finally, DES low eutectic solvent was added to the cooking container and fully mixed at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0031] (2) The cooked cellulose was bleached in a bleaching solution. The bleaching agent was sodium hypochlorite. The bleaching aid was aminosulfonic acid with a purity of 99.0wt%. The amount of aminosulfonic acid added was 15 g / kg. The bleaching time was 60 min and the bleaching temperature was 70°C. The cellulose concentration in the desanding process was 2%, and the desanding pressure was 0.28 MPa. After desanding, a deashing iron agent (NaPO3)6 was added. The amount of the deashing iron agent was 0.05% of the amount of absolutely dry waste wood. Then the cellulose concentration in the concentrator was controlled to 3%. After concentrating, it was formed into paper by a papermaking machine. The amount of desalted water sprayed was 40 m 3 / h, and finally obtain wood cellulose.
[0032] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 11.1 mPa.s, cellulose content is 91.1%, polypentose content is 3.98%, and reaction performance is <250 s.
[0033] Example 2 This embodiment provides a lignocellulose based on waste biomass materials, which is prepared according to the following steps: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 60 g / L and a volume of 4 L of alkali solution, and keep it at 170°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 1.5 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0034] (2) The cooked cellulose was bleached in a bleaching solution. The bleaching agent was sodium hypochlorite. The bleaching aid was aminosulfonic acid with a purity of 99.0wt%. The amount of aminosulfonic acid added was 15 g / kg. The bleaching time was 60 min and the bleaching temperature was 70°C. The cellulose concentration in the desanding process was 2%, and the desanding pressure was 0.28 MPa. After desanding, a deashing iron agent (NaPO3)6 was added. The amount of the deashing iron agent was 0.05% of the amount of absolutely dry waste wood. Then the cellulose concentration in the concentrator was controlled to 3%. After concentrating, it was formed into paper by a papermaking machine. The amount of desalted water sprayed was 40 m 3 / h, and finally obtain wood cellulose.
[0035] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.4 mPa.s, cellulose content is 91.8%, polypentose content is 3.81%, and reaction performance is <250 s.
[0036] Example 3 This embodiment provides a lignocellulose based on waste biomass materials, which is prepared according to the following steps: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 170°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 1.5 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0037] (2) The cooked cellulose was bleached in a bleaching solution. The bleaching agent was sodium hypochlorite. The bleaching aid was aminosulfonic acid with a purity of 99.0wt%. The amount of aminosulfonic acid added was 15 g / kg. The bleaching time was 60 min and the bleaching temperature was 70°C. The cellulose concentration in the desanding process was 2%, and the desanding pressure was 0.28 MPa. After desanding, a deashing iron agent (NaPO3)6 was added. The amount of the deashing iron agent was 0.05% of the amount of absolutely dry waste wood. Then the cellulose concentration in the concentrator was controlled to 3%. After concentrating, it was formed into paper by a papermaking machine. The amount of desalted water sprayed was 40 m 3 / h, and finally obtain wood cellulose.
[0038] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.6 mPa.s, cellulose content is 92.5%, polypentose content is 3.58%, and reaction performance is <250 s.
[0039] Example 4 This embodiment provides a lignocellulose based on waste biomass materials, which is prepared according to the following steps: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 166°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2.0 mL / kg. The amount of cobalt chloride added is 1.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0040] (2) The cooked cellulose was bleached in a bleaching solution. The bleaching agent was sodium hypochlorite. The bleaching aid was aminosulfonic acid with a purity of 99.0wt%. The amount of aminosulfonic acid added was 15 g / kg. The bleaching time was 60 min and the bleaching temperature was 70°C. The cellulose concentration in the desanding process was 2%, and the desanding pressure was 0.28 MPa. After desanding, a deashing iron agent (NaPO3)6 was added. The amount of the deashing iron agent was 0.05% of the amount of absolutely dry waste wood. Then the cellulose concentration in the concentrator was controlled to 3%. After concentrating, it was formed into paper by a papermaking machine. The amount of desalted water sprayed was 40 m 3 / h, and finally obtain wood cellulose.
[0041] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.5 mPa.s, cellulose content is 92.4%, polypentose content is 3.37%, and reaction performance is <250 s.
[0042] Example 5 This embodiment provides a lignocellulose based on waste biomass materials, which is prepared according to the following steps: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 162°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2.0 mL / kg. The amount of cobalt chloride added is 1.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0043] (2) The cooked cellulose was bleached in a bleaching solution. The bleaching agent was sodium hypochlorite. The bleaching aid was aminosulfonic acid with a purity of 99.0wt%. The amount of aminosulfonic acid added was 15 g / kg. The bleaching time was 60 min and the bleaching temperature was 70°C. The cellulose concentration in the desanding process was 2%, and the desanding pressure was 0.28 MPa. After desanding, a deashing iron agent (NaPO3)6 was added. The amount of the deashing iron agent was 0.05% of the amount of absolutely dry waste wood. Then the cellulose concentration in the concentrator was controlled to 3%. After concentrating, it was formed into paper by a papermaking machine. The amount of desalted water sprayed was 40 m 3 / h, and finally obtain wood cellulose.
[0044] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 11.0 mPa.s, cellulose content is 91.6%, polypentose content is 3.23%, and reaction performance is <250 s.
[0045] Example 6 This embodiment provides a wood cellulose, which is different from the embodiment 1 in that: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 80 g / L and a volume of 4 L of alkali solution, and keep it at 170°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0046] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.5 mPa.s, cellulose content is 91.4%, polypentose content is 3.87%, and reaction performance is <250 s.
[0047] Example 7 This embodiment provides a wood cellulose, which is different from the embodiment 2 in that: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 60 g / L and a volume of 4 L of alkali solution, and keep it at 170°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0048] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.1 mPa.s, cellulose content is 92.1%, polypentose content is 3.76%, and reaction performance is <250 s.
[0049] Example 8 This embodiment provides a wood cellulose, which is different from the embodiment 3 in that: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 170°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0050] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 9.7 mPa.s, cellulose content is 94.5%, polypentose content is 3.06%, and reaction performance is <250 s.
[0051] Example 9 The lignocellulose provided in this embodiment is different from that in embodiment 4 in that: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 166°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2.0 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0052] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.1 mPa.s, cellulose content is 92.8%, polypentose content is 3.24%, and reaction performance is <250 s.
[0053] Example 10 The lignocellulose provided in this embodiment is different from that in embodiment 5 in that: (1) Place 1 kg of waste wood in a forced air drying oven and dry it at 55°C for later use. Then put the dried waste wood into a cooking container, steam it at 170°C for 2 h, and then discharge the steam in the container. Then add a sodium hydroxide solution with a concentration of 40 g / L and a volume of 4 L of alkali solution, and keep it at 162°C for 3 h. Then add polyethylene glycol and cobalt chloride catalyst, wherein the degree of polymerization of polyethylene glycol is 7-15, and the volume / mass ratio of polyethylene glycol to waste wood raw material is 2.0 mL / kg. The amount of cobalt chloride added is 2.0 g / kg, and keep it at 160°C for 0.5 h. Finally, add DES low eutectic solvent into the cooking container and mix it thoroughly at 70°C to obtain primary lignocellulose. Among them, the mass ratio of DES low eutectic solvent and waste wood is 3:1, the HBA component is CoCL2, the HBD component is a mixture of choline chloride, citric acid and glycerol in a molar ratio of 1:1.2:0.8, and HBA:HBD=1:2 (mass ratio).
[0054] The physicochemical indicators of the wood cellulose obtained in this example are as follows: cuprammonia viscosity is 10.6 mPa.s, cellulose content is 92.3%, polypentose content is 3.21%, and reaction performance is <250 s.
[0055] Test Example 1 In this test example, the effects of alkali solution concentration and additive dosage on the physicochemical indices of lignocellulose were studied respectively. In Examples 1 to 3, different alkali solution concentrations (i.e., the concentrations of sodium hydroxide solution were 80, 60, and 40 g / L) were used to study the effect of alkali solution concentration on the physicochemical indices of lignocellulose. In Examples 1 to 3 and Examples 6 to 8, different additive dosages were used to study the effect of additives on the physicochemical indices of lignocellulose.
[0056] When the volume / mass ratio of the additive polyethylene glycol to the waste wood raw material was 1.5 mL / kg, the effect of alkali solution concentration on the physicochemical indexes of lignocellulose was studied at different alkali solution concentrations (i.e., the concentration of sodium hydroxide solution was 80, 60, and 40 g / L). The experimental results show that when the concentration of sodium hydroxide solution was 80 g / L, the lignocellulose copper-ammonia viscosity was 11.1 mPa.s, the cellulose content was 91.1%, the polypentose content was 3.98%, and the reaction performance was <250 s; when the concentration of sodium hydroxide solution was 60 g / L, the lignocellulose copper-ammonia viscosity was 10.4 mPa.s, the cellulose content was 91.8%, the polypentose content was 3.81%, and the reaction performance was <250 s; when the concentration of sodium hydroxide solution was 40 g / L, the lignocellulose copper-ammonia viscosity was 10.6 mPa.s, the cellulose content was 92.5%, the polypentose content was 3.58%, and the reaction performance was <250 s.
[0057] The concentration of sodium hydroxide solution is 40 g / L, and the copper ammonia viscosity, cellulose content and polypentose content of lignocellulose are excellent, reaching the standards for use in the lignocellulose industry.
[0058] When the volume / mass ratio of the additive polyethylene glycol to the waste wood raw material was 2 mL / kg, the effect of alkali solution concentration on the physicochemical indicators of lignocellulose was studied at different alkali solution concentrations (i.e., the concentration of sodium hydroxide solution was 80, 60, and 40 g / L). The experimental results show that the lignocellulose copper-ammonia viscosity obtained when the concentration of sodium hydroxide solution was 80 g / L was 10.5 mPa.s, the cellulose content was 91.4%, the polypentose content was 3.87%, and the reaction performance was <250 s. The lignocellulose copper-ammonia viscosity obtained when the concentration of sodium hydroxide solution was 60 g / L was 10.1 mPa.s, the cellulose content was 92.1%, the polypentose content was 3.76%, and the reaction performance was <250 s. The lignocellulose copper-ammonia viscosity obtained when the concentration of sodium hydroxide solution was 40 g / L was 9.7 mPa.s, the cellulose content was 94.5%, the polypentose content was 3.06%, and the reaction performance was <250 s.
[0059] By increasing the volume / mass ratio of the additive polyethylene glycol to the waste wood raw materials, the two major indicators of wood cellulose copper ammonia viscosity and polypentose are optimized and the cellulose content is increased.
[0060] Test Example 2 This test example studies the effects of alkali solution reaction temperature and catalyst addition amount on various indicators of lignocellulose. Among them, the catalyst addition amount in Example 4 is 1.0 g / kg, and the alkali solution reaction temperature is 166°C; the catalyst addition amount in Example 5 is 1.0 g / kg, and the alkali solution reaction temperature is 162°C; the catalyst addition amount in Example 9 is 2.0 g / kg, and the alkali solution reaction temperature is 166°C; the catalyst addition amount in Example 10 is 2.0 g / kg, and the alkali solution reaction temperature is 162°C.
[0061] From the test results, it can be seen that after the cooking temperature is 166℃ and the catalyst addition amount is selected to be 2.0 g / kg, the copper ammonia viscosity, cellulose content and polypentose content of the cellulose are excellent, reaching the standards for use in the cellulose industry.
[0062] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing lignocellulose based on waste biomass materials, characterized in that: The following steps are involved: S1. After drying, steaming, alkali solution reaction and cooking of waste wood, a DES low eutectic solvent is added and mixed to obtain primary lignocellulose, wherein a catalyst and a polyether water-soluble organic additive are added during the cooking, and the catalyst is a metal chloride catalyst or a metal bromide catalyst; S2. The primary lignocellulose is bleached, sanded, concentrated and formed into paper, thereby obtaining lignocellulose.
2. The preparation method according to claim 1, characterized in that: In step S1, the waste wood is selected from one or more of cypress, elm, eucalyptus, and locust wood, and the moisture content of the waste wood after drying is less than 5.0%.
3. The preparation method according to claim 1, characterized in that In step S1, the steaming step is: putting the dried waste wood into a cooking container, steaming at 160° C. to 175° C. for 1 to 4 hours, and then discharging the steam in the cooking container.
4. The preparation method according to claim 1, characterized in that In step S1, the alkali solution used in the alkali solution reaction is selected from one of sodium hydroxide solution, potassium hydroxide solution, and calcium hydroxide solution, the concentration of the alkali solution is 30-120 g / L, the temperature of the alkali solution reaction is 155° C.-175° C., and the alkali solution reaction time is 3-5 h.
5. The preparation method according to claim 1, characterized in that In step S1, the polyether water-soluble organic additive is selected from one of polyethylene oxide and polyethylene glycol, the amount ratio of the polyether water-soluble organic additive to the waste wood is (0.5-10): (1.5-3) mL / kg, the catalyst is selected from one of nickel chloride, cobalt chloride, ferrous chloride, cobalt bromide, and copper bromide, and the addition amount thereof is 0.2-5.0 g / kg, the cooking temperature is 100°C-160°C, and the cooking time is 0.5-1 h.
6. The preparation method according to claim 1, characterized in that In step S1, the DES low eutectic solvent includes an HBA component and an HBD component, the HBA component is CoCL2, NaCL or ChCL, the HBD component is an acid substance, the mass ratio of the HBA component to the HBD component is 1:1~2, the mixing temperature is 50~80°C, and the mixing time is 20~45 min.
7. The preparation method according to claim 1, characterized in that In step S2, the bleaching solution used for bleaching includes a bleaching agent and a bleaching aid, the bleaching agent is selected from any one of sodium hypochlorite, hydrogen peroxide, thiourea dioxide, and chlorine dioxide, the bleaching aid is selected from any one of aminosulfonic acid, tetraacetylethylenediamine, and alkyl polyoxyethylene ether, the bleaching temperature is 30°C to 70°C, and the bleaching time is 30 to 60 min.
8. The preparation method according to claim 1, characterized in that In step S2, the desanding step is: controlling the concentration of wood cellulose in the slurry to 0.5%~2%, the desander pressure to 0.28~0.5 MPa for desanding, and adding a deashing iron agent after desanding, wherein the amount of the deashing iron agent is 0.01%~0.05% of the mass of the dried waste wood.
9. The preparation method according to claim 1, characterized in that In step S2, the steps of concentrating and forming are as follows: controlling the concentration of lignocellulose in the concentrator to be 3% to 5%, and using desalted water to form lignocellulose after concentration, wherein the spraying amount of desalted water is 25 to 40 m 3 / h.
10. A lignocellulose based on waste biomass material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for separating three components of cellulose, hemicellulose and lignin in plant fiber raw materials
CN108660837A
Method for preparing high-yield dissolving pulp by using eutectic solvent
CN112482069A
Juncao spinning pulp as well as preparation method and application thereof
CN115584565A
Production method of acetified fiber pulp
CN118007462A
Method for optimizing quality of biomass slurry based on biological enzyme and preparation system thereof
CN118745678A
Cited By
Microwave-assisted deep-eutectic solvent extraction-in-situ carboxymethylation modified cellulose integrated preparation method, modified cellulose and application
CN121736124A
